SKIA-SH: A Symmetric Key-Based Improved Lightweight Authentication Scheme for Smart Homes. (12th February 2022) - Alzahrani, Bander A.; Barnawi, Ahmed; Albarakati, Abdullah; Irshad, Azeem; Khan, Muhammad Asghar; Chaudhry, Shehzad Ashraf
Abstract : Being one of the finest applications of the IoT, smart homes (SHs) with an aim to improve quality of life are taking over the traditional lifestyles. The entities within a SH communicate with each other and with the environment including the users to transform daily life seamlessly enjoyable and easy. However, owing to the public communication infrastructure, the advantages of SH are subject to security and privacy issues. Recently, Yu et al. presented a privacy and security solution for SH environment. The scheme of Yu et al. is based on lightweight symmetric key functions. Although the scheme of Yu et al. exhibits the lightweight property, it is proven in this paper that their scheme cannot provide mutual authentication due to a crucial design fault. An improved scheme using symmetric key functions for SH (SKIA-SH) is proposed in this paper. The security of the proposed scheme is furnished through formal BAN logic followed by brief discussion on security attribute provision of the proposed SKIA-SH. The comparisons show that the proposed SKIA-SH provides the required security on the cost of slight increase in computation and communication costs. The simulation results show that the SKIA-SH completes an authentication round by exchanging 216 bytes in just 5.34 ms.